PROSES TRANSFORMASI PADA WEBTOON PASUTRI GAJE KE DALAM FILM PASUTRI GAJE - Dini Gustiani AR; David Setiadi; Asep Firdaus (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study is motivated by the growing adaptation of literary works into films, which has generally focused on novels, while adaptations from webtoons remain relatively limited. The aim of this research is to examine the process of ekranisasi in the webtoon Pasutri Gaje by Annisa Nisfihani and its film adaptation Pasutri Gaje directed by Fajar Bustomi. This study employs a qualitative approach, using the webtoon and the film as the primary data sources. The analysis focuses on ekranisasi by examining forms of reduction and addition that occur during the adaptation process. Data were collected through observation, note-taking, and documentation, and were analyzed descriptively by comparing the two media. The findings indicate that the adaptation from webtoon to film involves both reductions and additions in several narrative elements, particularly in the plot, supporting characters, and settings, carried out to accommodate the film’s duration and visual requirements.